Interactive influence of extracellular polymeric substances (EPS) and electrolytes on the colloidal stability of silver nanoparticles - Fernando, Ishara (2022)
The colloidal stability of silver nanoparticles (AgNPs) was evaluated using time-resolved dynamic light scattering, electrophoretic mobility and dissolved silver concentration in the presence of common monovalent or divalent electrolytes and extracellular polymeric substances (EPS). The colloidal stability of AgNPs was significantly affected by the electrolyte. A relatively lower critical coagulation concentration (CCC) was recorded for AgNPs in the divalent electrolytes. Three types of EPS namely, soluble EPS (SBEPS), loosely bound EPS (LB-EPS) and tightly bound EPS (TB-EPS) extracted from activated sludge, were added into electrolytes that contain AgNPs to investigate the potential different impacts on AgNP transformation. Overall, the presence of all the types of EPS reduced the aggregation rate and increased the CCC values in NaNO3 and low concentrations of CaĲNO3)2 (0.05–10 mM) solutions. When the NaNO3 concentration was higher than 12 mM, the attachment efficiency of AgNPs was below one, suggesting that the EPS adsorbed on the AgNPs resulted in steric repulsion and stabilizing the AgNP suspension effectively. However, the presence of EPS increased the rate of aggregation of AgNPs at higher CaĲNO3)2 concentrations (10–40 mM), which can be due to the aggregation of the dissolved EPS via intermolecular bridge linking of the AgNPs and aggregates together. Among the three types of EPS used in the study, LBEPS effectively stabilized the AgNPs irrespective of the electrolyte mainly due to the lower presence of the hydrophilic dissolved organic matter in LB-EPS. These results provide important insights into understanding the interactive impact of EPS and ions on AgNP transformation.